On the Synchronous Characteristics of the Diphthongoid աւ (aṷ) in Old Armenian - Petrosyan, Vardan (Bulletin of Yerevan University B: Philology, 2026)
In Old  Armenian, the diphthongoid  աւ (aṷ), which fits the “V + S” pattern (Vowel + Semivowel), can appear in all three possible positions: at the beginning, in the middle and at the end.  In the first two positions (word-initial and middle), it typically comes before a consonant (compare: աւգուտ, աւդ, աւծումն, աւտար, etc.; արաւր, ծանաւթ, հաւտ, եղբաւր, etc.). In final position, it appears in a conditionally closed syllable. This is because the semivowel ւ (ṷ) in Old Armenian could not function as a syllabic nucleus. Thus,  a syllable ending in ւ (ṷ) could not be considered open. Unlike in the word-initial position, where աւ (aṷ) is simply a sequence of phonetic (or phonemic) elements that make up the word and where the components are tightly linked in pronunciation, in the middle and final positions, it could also take on a grammatical role, i.e. it could act as a morphological marker. (Comp.հաւր – genitive/dative singular of հայր (“father”),ազգաւ – instrumental singular of ազգ (“nation”), Հոմերաւ – instrumental singular of Հոմերոս (“Homer”), etc.) According to traditional Armenian linguistics, the relationship between the semivowel ւ (ṷ) and the following vowel when occurring between two vowels was considered a combination of two separate phonemes. However, we believe that even in this position the semivowel forms a diphthongic structure in accordance with  the “V + S” pattern. (Comp. ա-ւագ, նա-ւազ, ա-ւեր, բե-ւեռ, բա-ւիղ, շա-ւիղ, թագա-ւոր, լուսա-ւոր, etc., where the diphthongoid ւա (ṷa), ւե (ṷe), ւի (ṷi), ւո (ṷo) are present.)
Keywords: synchronous description; diphthongoid, phonemоid; phonological function; phonological opposition; Acharian; Aghayan